Promise Canyon - Carr, Robyn; Copyright Paperback Collection (Library of Congress) (Don Mills, Ont. : MIRA, 2011)
Clay Tahoma, Virgin River's new veterinary assistant, is welcomed by everyone in town except Lilly Yazhi, who believes that his down-to-earth attitude and rugged sex appeal is an act to charm wealthy women like his ex-wife.
Keywords: Indians of North America -- Fiction; Animal health technicians -- Fiction; Horses -- Fiction; Man-woman relationships -- Fiction; California, Northern -- Fiction; Love stories